Carbon footprint savings from free fare public transport policies. The case of Marbella. - Maeso-González, Elvira; González-Sánchez, Guadalupe; Olmo-Sánchez, María Isabel; Solano-Martos, José Francisco (My University, 2023)
One of the main goals of free fare public transport policy is to reduce car use by promoting other more sustainable modes of transport. The aim of this work is to develop a methodology that allows us to evaluate the carbon footprint savings derived from the implementation of these policies based on the CO2 emissions avoided by the trips captured from the car mode. To do this, we will study the case of the city of Marbella, comparing the evolution of the demand for bus trips, before and after COVID-19, with other cities that do not have free public transport. As a result, a total saving of 835.75 tonnes of CO2 emissions to the at-mosphere is estimated for the study period 2019-2022. This methodology is a useful tool to measure the effectiveness of these policies in terms of environmental impact.
Keywords: Transporte - Aspectos ambientales; Free Fare Public Transport; FFPT; Carbon footprint; Environmental impact; Bus